How Psychological Well-Being during Covid-19 Pandemic in Faculty Teacher Training and Education Ahmad Dahlan University? - Dody Hartanto; Caraka Putra Bhakti; Zaenab Amatillah Rodhiyya; Cucu Kurniasih (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The Covid-19 pandemic has impacted the learning process. Changes in interaction patterns in the learning process from face-to-face laerning to online learning affects the psychological well-being of students. This study aimed to determine the description of psychological well-being in students of the Faculty of Teacher Training and Education, Ahmad Dahlan University. For college students, a crucial psychological aspect is psychological well-being, which contributes to academic success and life. This article uses the method of literature study and survey by collecting data from 318 students of Teacher Training and Education Faculty. The data is then analyze using the Ryff’s Psychological Well-Being (RPWB) scale adapted into Indonesian by Amalia. The results showed that of the 318 respondents divided into five category, there are very high category, high category, middle category, low category, and shallow category. The highest number was in high category. However, if the other category were included, the overall picture of Ahmad Dahlan University Faculty Teacher Training and Education students is in the medium category. The result implicates that students still need guidance to improve their psychological well-being condition in order to maintain their college life and personal life during pandemic